A primary cilium in oligodendrocytes: a fine structure signal of repairs in thalamic Osmotic Demyelination Syndrome (ODS). (4th March 2021) - Gilloteaux, Jacques; Bouchat, Joanna; Bielarz, Valery; Brion, Jean-Pierre; Nicaise, Charles
ABSTRACT: A murine osmotic demyelination syndrome (ODS) model of the central nervous system included the relay thalamic ventral posterolateral (VPL) and ventral posteromedial (VPM) nuclei. Morphologic comparisons between treatments have revealed oligodendrocyte changes and, already 12 hours following the osmolality restoration, some heavily contrasted oligodendrocytes formed a unique intracellular primary cilium. This unique structure, found in vivo, in mature CNS oligodendrocytes, could account for a local awakening of some of the developmental proteome as it can be expressed in oligodendrocyte precursor cells. This resilience accompanied the emergence of arl13b protein expression along with restoration of nerve cell body axon hillocks shown in a previous issue of this journal. Additionally, the return of several thalamic oligodendrocyte fine features (nucleus, organelles) was shown 36 h later, including some mitosis. Those cell restorations and recognized translational activities comforted that local repairs could again take place, due to oligodendrocyte resilience after ODS instead or added to a postulated immigration of oligodendrocyte precursor cells distant from the sites of myelinolysis.